Prenatal Risk Assessment for Severe Thalassemia in Public Health Region 7, Thailand - Vimolsarte, Sutudsanee; Vimolsarte, Charlie; Aomsin, Rassame; Punthanaprated, Udomkiat (Journal of Health Science of Thailand, 2017)
Thalassemia disease is a group of inherrited autosomal recessive blood disorder. Thai national policy for prevention and control of thalassemia has emphasized on 3 severe thalassemia diseases: homozygous β-thalassemia, β-thal/Hb E and hemoglobin Bart’s hydrop fetalis in order to reduce the disease incidence. In this regard, the Regional Medical Science Center 7, Khon Kaen, has implemented the Ministry of Public Health policy since 1997. The objective of this study was to assess the risk of severe thalassemia among pregnant women and their spouse in the Public Health Region 7 during 2011-2014. The testing results of blood samples sent from health facilities in the region during the studied period were collected and analyzed. As for the results, there were altogether 24,192 samples underwent Hb typing to detect α-thalassemia 1 trait and β-thalassemia mutations; and abnormal hemoglobin was detected in 10,298 couples or 67.1% of the samples. The detection rate of Hb Bart’s Hydrop fetalis, Homozygous β-thalassemia and β-thalassemia/HbE was found to be 1.1%, 0.01% and 2.2% respectively. Screening for thalassemia cariers revealed 14.0% of α-thalassemia 1 trait SEA deletion and 0.9% of Thai deletion. Testing for 109 cases of β-thalassemia trait revealed 73.4% of β-thalassemia mutation, and 75.0% were of severe type. In addition, abnormal hemoglobin was found in 18 cases.